Current status and prospects of diabetes mellitus induced erectile dysfunction: A bibliometric and visualization study - Zhang, Lei; Bao, Binghao; Guo, Jianqiang; Qin, Zhongjian; Huang, Haonan; Chen, Lu; Liu, Baoxing (Frontiers in Endocrinology, 2023)
Background: The prevalence of diabetes mellitus-induced erectile dysfunction (DMED) has recently increased, which has prompted numerous DMED studies. Here, we conduct a bibliometric analysis of relevant literature in the field of DMED and to discuss the research hotspots and future development directions. Methods: The Web of Science Core Collection database was searched for literature on DMED, and literature characterization including the number of articles, journals, countries/regions, institutions, authors, keywords, and other information was performed using VOS viewer and CiteSpace software. In addition, Pajek software was used for visual map adjustment, and GraphPad Prism was used to generate line graphs. Results: A total of 804 articles concerning DMED were included in this study. The Journal of Sexual Medicine issued the most documents(92 articles). The United States and China were in the leading position in the field of DMED research, and cross-institutional collaboration on DMED research worldwide needs to be further strengthened. Ryu JK were the authors with the highest number of documents issued (22 articles) while Bivalacqua TJ was the author with the most co-citated(249 co-citated). The keywords analysis shows that the main research hotspots in the field of DMED were mechanism discussions and disease treatment and management. Conclusions: Global research on DMED is expected to increase further. The investigation of the mechanism of DMED and the exploration of new therapeutic means and targets are the focus of future research.